Echo Parameters for Differential Diagnosis in Cardiac Amyloidosis: A Head-to-Head Comparison of Deformation and Nondeformation Parameters. (March 2017) - Pagourelias, Efstathios D.; Mirea, Oana; Duchenne, Jürgen; Van Cleemput, Johan; Delforge, Michel; Bogaert, Jan; Kuznetsova, Tatyana; Voigt, Jens-Uwe
Abstract : Background—: A plethora of echo parameters has been suggested for distinguishing cardiac amyloidosis (CA) from other causes of myocardial thickening with, however, scarce data on their head-to-head comparison. This study aimed at comparing the diagnostic accuracy of various deformation and conventional echo parameters in differentiating CA from other hypertrophic substrates, especially in the gray zone of mild hypertrophy (maximum wall thickness ⩽16 mm) or normal ejection fraction (EF). Methods and Results—: We included 100 subjects, of which 40 were patients with newly diagnosed, biopsy-proven CA (65.5±10.8 years, 65% male, 62.5% amyloidosis light chain [AL] type), 40 patients with hypertrophic cardiomyopathy matched for demographics and maximum wall thickness (60.1±14.8 years, 85% male), and 20 hypertensives with prominent myocardial remodeling. Quantifiable conventional morphological and functional parameters along with multidimensional strain and strain-derived ratios indices, previously suggested to diagnose CA, were analyzed. EF global longitudinal strain ratio showed the best performance to discriminate CA (area under the curve, 0.95; 95% confidence intervals, 0.89–0.98; P <0.00005). Traditional echo indices showed overall low sensitivities and high specificities (among them myocardial contraction fraction ratio had the highest area under the curve, 0.80; 95% confidence intervals, 0.7–0.87; P <0.0001). In the challenging subgroups (maximum wall thickness ⩽16 mm and EF>55%), EF global longitudinal strain ratio remained the best predicting parameter of CA diagnosis (multiple logistic regression models P <0.00005 and P =0.0002, respectively) independent of the CA type. Conclusions—: Our study demonstrated that in patients with thickened hearts, EF global longitudinal strain ratio has the best accuracy in detecting CA, even among the most "challenging" patient subgroups as those with mild hypertrophy and normal EF. Abstract : Supplemental Digital Content is available in the text.